A disciplina prática de ensino de literatura na formação do professor - Franco, Ana Maria (2010)
The teaching of Literature has found many questionings, as related to the subscription of the students in the construction of a reading culture, as about the current reality of the teaching of Literature. The process of formation of critic readers at the elementary school and high school, generally, has had impediments mainly for the non-valuableness of the teaching of Literature, not giving it the considerable importance that it has in the school curriculum. We notice that, in many cases, there is not an effective worry about the formation of the students as readers, but a systematic and logical teaching of Literature, with plenty of ready interpretations and analyses, closed and focused on the teacher's figure. Most of the time, the students become mere receivers of ready senses for the objects of reading, it means there is no space for the students to construct their reflections from their interactions with the world. Due to this reality about the unvaluable of the teaching of Literature, observed at the elementary school and high school, the importance of the formation of teachers in this field, initiated at the academy, is questioned, because the discoursive crossings provided by school come over the intership subjects, like Teaching of Literature Practice , what makes appear the discredit on the possibility of changes in the teaching of Literature, connecting the academic theories to the teaching practice. In this current project, we look for discussing the bases of teaching of Literature at the elementary school and high school, and the importance of the formation of teachers who know how to connect the theory to the practice. Our focus on the analyses is the formation of the pre-service teacher in the academic subject Teaching of Literature Practice and our corpus is formed by pre-service teachers that, when they concluded this subject, have reflected about their constitution as Literature teachers and about the teaching of the academic subject in their school experiences, answering an AREDA Questionnaire. We do not have the intention in this project to observe the linguistic materiality separated in each participant. We attempted, throughout the disjoint of the collected speeches, to select them into discoursive sequences, protecting the pre-service teachers' identity, who helped the research. We also attempted to demonstrate throughout the discoursive sequences which image of Literature teacher the undergraduate constructs after studying the subject Teaching of Literature Practice . We look into the relationship of the pre-service teachers with Literature, with teaching and how important the experiences as Literature students are for their formation as teacher and for the construction of their relationship with the subject and with reading. We have as theoretical bases the French Discoursive Analysis, Michel Foulcault's studies, mainly based on his reflections about discipline. We also take apart official documents, like: LDB , PCNs and Pedagogic Politic Project of Languages Course . We include some theoretical references used in the subject Teaching of Literature Practice , which make part of the academic knowledge of the pre-service Literature teachers. Our project do not intend only to reach the academic teaching formation , but also provoke on the in-service teachers reflections about the current reality of Literature teaching and promote discussions about what can be done to get some changes involving the reading identification from the elementary school and high school students.